Health-Related Quality of Life During Postoperative Chemoradiotherapy with Oral Uracil-Tegafur and Leucovorin in Rectal Cancer Patients - ATASOY, BESTE MELEK; DANE, FAYSAL; YUMUK, PERRAN FULDEN (H G E UPDATE MEDICAL PUBLISHING S A, 2013)
Background/Aims: The objective of this study was to report on the quality of life of locally advanced rectal cancer patients that were treated with uracil-tegafur (UFT)/leucovorin (LV)-based concurrent chemoradiotherapy. Methodology: Twenty-five patients were enrolled into this prospective study. Radiotherapy (50.4Gy) was given with concurrent UFT (300mg/m(2)/day) and LV (30mg/day). Turkish versions of EORTC-QLQC30 and EORTC QLQCR38 were applied at the beginning (HROoL-1) and at the end (HRQoL-2) of chemoradiotherapy. Paired samples t-test was used to compare the difference of means for each scale between HRQoL1 and HRQoL2 and p values <0.05 were considered statistically significant. Results: Study compliance was 80.6%. From baseline to the end of chemoradiotherapy, the mean scores of dyspnea (p=0.006) diarrhea (p=0.005) and micturition (p=0.005) increased significantly. Chemotherapy side effects also increased at the end of therapy (p=0.07). Seventy-six percent (76%) of male patients replied to questions related to sexual problems and functions, whereas no female patients replied. Conclusions: Although, diarrhea and micturition are the major problems, quality of life scores indicate that concurrent oral fluoropyrimidine-based chemoradiotherapy is a feasible treatment.
Keywords: Chemoradiotherapy; Concomitant; Health-related quality of life; Rectal cancer; UFT; ADJUVANT THERAPY; PHASE-III; RADIOTHERAPY; FLUOROURACIL; MULTICENTER; QLQ-C30; UFT